ANALISIS KEPUASAN PENGGUNA APLIKASI SI JEMPOL MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE (UEQ) PADA JASDAM II / SRIWIJAYA - Amanda Putri, Febrina; Yulianingsih, Evi (JIMR : Journal Of International Multidisciplinary Research, 2025)
The research aims to analyze the user experience of the Si Jempol application in the Jasdam II/Sriwijaya environment. The research uses the User Experience Questionnaire (UEQ) method to include various dimensions of User Experience (UX) which include attractiveness, clarity, efficiency and other relevant aspects. There are six measurement scales in the User Experience Questionnaire (UEQ) which includes a total of 26 question items, where each element is analyzed based on the dimensions to be measured. The Si Jempol application got positive appeal, got good clarity in interface clarity, showed efficiency in speed and ease of use, had a low score on precision, had a high score on stimulation and had a low score on novelty. The results of the research show that the Si Jempol application overall received a score in the Very Good category but one scale obtained results in the Good category based on the User Experience Questionnaire (UEQ) method. Developers are advised to improve the Novelty and Efficiency aspects so that applications increasingly meet optimal user experience standards so that applications remain stable and can be accessed more easily